2019
DOI: 10.1039/c9qm00112c
|View full text |Cite
|
Sign up to set email alerts
|

Trap passivation and efficiency improvement of perovskite solar cells by a guanidinium additive

Abstract: Incorporation of an effective additive 1,3-diaminoguanidine monohydrochloride in MAPbI3 film can increase the grain size and reduce trap density, consequently increasing the carrier lifetime and reducing charge recombination, leading to an improved efficiency from 19.1% to 20.3% in a p–i–n structured solar cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
2
26
0
Order By: Relevance
“…This is consistent with the previous report that there is almost no J–V hysteresis for perovskite solar cells using a similar device stack. [ 26 ] Nevertheless, the R–V curves are strongly influenced by scan parameters, showing more significant hysteresis with slower scan rate and with V ( t = 0) = −0.2 V. The different hysteresis behavior in J–V and R–V curves is in line with the larger change in EL intensity than current density, as shown in Figure 1. To give a clearer comparison, we have plotted the J–V (Figure S5, Supporting Information) and R–V (Figure S6, Supporting Information) curves separately both in linear and semi‐log scales.…”
Section: Figurementioning
confidence: 74%
“…This is consistent with the previous report that there is almost no J–V hysteresis for perovskite solar cells using a similar device stack. [ 26 ] Nevertheless, the R–V curves are strongly influenced by scan parameters, showing more significant hysteresis with slower scan rate and with V ( t = 0) = −0.2 V. The different hysteresis behavior in J–V and R–V curves is in line with the larger change in EL intensity than current density, as shown in Figure 1. To give a clearer comparison, we have plotted the J–V (Figure S5, Supporting Information) and R–V (Figure S6, Supporting Information) curves separately both in linear and semi‐log scales.…”
Section: Figurementioning
confidence: 74%
“…The upward shift of the VBM of the 2 mg PEAI deposited sample improves its energy band alignment with that of the HTL, Spiro‐OMeTAD, potentially contributing to the reduced voltage losses compared to the reference sample (see Figure c). [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported that GUA cation can form strong hydrogen bonds with the halides that may passivate the defects and improve the device performance. [46,47] The capacitance response of MAPbI 3 and MAGUA devices depicts the similar frequency response in the low-and high-frequency regions, but C LF increases significantly as bias approaches to V OC for MAGUA PSC (see for more detail in the study by Kubicki et al [45] ). In line with the results on IPA-treated PSCs, we also found that a higher value of C LF not necessary leads to higher recombination.…”
Section: Effect Of Perovskite Composition On the Low-frequency Arc In Eis Of Pscmentioning
confidence: 93%